Pemanfaatan Tanaman Lokal Biji Kelor (Moringa Oleifera) sebagai Biokoagulan pada Proses Penjernihan Mata Air di Desa Maurisu Kabupaten Timor Tengah Utara - Maria Imaculata Mali; Maria Magdalena Kolo; Marselina Theresia Djue Tea (Fakultas Pertanian, Universitas Timor, 2022)
This study aims to determine the activity and ability of Moringa oleifera seeds as biocoagulants in reduncing the levels of each water parameters in the drinking water purification process and to determine the optimum concentration od effective biocoagulants to reduce each water parameters in drinking water purification. This research was conducted in the Laboratory of F aperta University Timor Kefamenanu, then further analyzed at the UPTD Health Laboratory of North Central Timor and UPTD Environment Services of Kupang. This study uses coagulation and flocculation methods with 1 treatment and 3 variations in concentration, namely 25 mg/L, 50 mg/L and 100 mg/L. The research material used was Moringa oleifera seed powder and the sample used was water from river springs. Tested parameters, physical parameters include turbidity, pH, temperature, total dissolved solids, total suspended solids. Chemical parameters include hardness, nitrate, nitrite, chlorine and parameters include E.coli and Coliform. The result showed that there was a decrease in each water parameters when Moringa oleifera seed powder was added to the watter sample. The highest percentage value of each water parameter is a decrease of turbidity 70,70%, pH 5,19%, temperatur 3,75%, hardness 37,50%, total dissolved solids 88,40%, total suspended solids 88,40%, chlorine 28%, nitrate 87,27%, nitrite 95%, E.coli 97,99% and Coliform 76,92%. Based on the results and discussion of this study, it can be concluded that biokoagulants of Moringa oleifera seed powder effective in reducing levels of parameters contained in water, both physical parameters, chemical parameter and biological parameters